The Implementation of Good Corporate Governance (GCG) in Mitigating Earnings Management Practices: A Systematic Literature Review - Rafi Fadhlurrhman; Isnuhardi Isnuhardi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) IBK Nitro, 2026)
This study aims to conduct a systematic review of global literature regarding the role of Good Corporate Governance (GCG) mechanisms in mitigating earnings management practices. The study use the Systematic Literature Review (SLR) method and PRISMA protocol, this research analyzes 25 reputable international journal articles published between 2020 and 2026. The analysis maps findings based on theoretical frameworks, GCG components, and oversight effectiveness. The results indicate that Agency Theory remains the dominant foundation in explaining the relationship between governance and earnings quality. The Audit Committee is identified as the most crucial GCG instrument, where independence and financial expertise of members are the primary determinants in detecting accrual discretion. However, this study also identifies the phenomenon of symbolic compliance, where governance fails to suppress earnings management if implementation is merely an administrative formality. Implications: This study emphasizes the importance of strengthening the substance of competence within internal corporate structures rather than merely fulfilling quantitative membership requirements